2013
DOI: 10.1016/j.jmb.2012.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mimetic CDK9 Inhibitors on HIV-1-Activated Transcription

Abstract: Potent antiretroviral therapy (ART) has transformed HIV-1 infection into a chronic manageable disease; however drug resistance remains a common problem that limits the effectiveness and clinical benefits of this type of treatment. The discovery of viral reservoirs in the body, in which HIV-1 may persist, has helped to explain why therapeutic eradication of HIV-1 has proved so difficult. In the current study we utilized a combination of structure based analysis of Cyclin/CDK complexes with our previously publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…We used U1 cells treated with cART for 5 days and subsequently treated with two different transcription inhibitors. We have previously shown that a mimetic of Tat (F07 number 13) and an ATP analog blocking CDK9 (CR8 number 13) can inhibit viral transcription (46). Both F07 number 13 and CR8 number 13 was used to treat U1 cells, and exosomes were isolated after 24 and 72 h using nanoparticles.…”
Section: Tar Rna Is Detected In Culture Supernatants Of Hiv-1-infectementioning
confidence: 99%
“…We used U1 cells treated with cART for 5 days and subsequently treated with two different transcription inhibitors. We have previously shown that a mimetic of Tat (F07 number 13) and an ATP analog blocking CDK9 (CR8 number 13) can inhibit viral transcription (46). Both F07 number 13 and CR8 number 13 was used to treat U1 cells, and exosomes were isolated after 24 and 72 h using nanoparticles.…”
Section: Tar Rna Is Detected In Culture Supernatants Of Hiv-1-infectementioning
confidence: 99%
“…We have developed chemical inhibitors that target host kinases as antiviral agents, which prevent the replication of several viruses, including the hepatitis C virus, dengue virus, and Sindbis virus (9)(10)(11)(12). To develop novel drugs, we have been recently focusing on cyclin-dependent protein kinases (CDKs), which are known to be used for virus replication (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the limitations of the animal model, 23 IM, and perhaps flavopiridol analogs 26 and recently developed mimetic CDK9 inhibitors, 27 may provide effective approaches for controlling HIV, particularly drug-resistant strains, in patients.…”
mentioning
confidence: 99%